A Game Between a Terrorist and a Passive Defender. Issue 3 (28th November 2017) - Baron, Opher; Berman, Oded; Gavious, Arieh
Abstract : In the last two decades, terrorism has become a major issue around the world. We analyze a continuous conflict between a terrorist (Terrorist) and a passive defender (Defender). Defender is passive because her actions can influence only the costs (damages) when Terrorist attacks. We focus on high‐trajectory fire attacks and passive responses to them in the conflict between Israel and the various terrorist groups in the Gaza Strip in accordance with scientific principles. We first consider three sources of data on this part of the conflict and based on these data we make several observations on the sustainability of cease fires, the use of technologies, different attacks, and the frequency of attacks, using high‐trajectory fire. To explain these observations, we present several stylized game theoretical models. Specifically, we consider single‐ and multi‐period games. In each period, Terrorist may attack Defender, who may in turn try to prevent damage. We show that given this conflict's political situation, our models are in agreement with the observations from the data. We also present an extension that considers an active defender. This extension also agrees with the observations from the data.